A Study to Assess Adolescents' Knowledge of Blood Donation in Selected Areas of Kerala - T, Anitha; JS, Anakha; PU, Devika; K, Geethu Das; N, Noufal; RS, Reshma Raveendran; KR, Shabna; AK, Sreethu; S, Subi; V, Vrindha (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
Blood donation has traditionally been portrayed in education as a selfless act. Three blood components that are helpful to a particular patient's needs may be obtained from a single donation alone. This study was conducted to evaluate adolescents’ knowledge of blood donation in selected regions of Kerala. The descriptive study was used to assess the level of adolescents’ knowledge regarding blood donation. The data was collected from 60 samples from selected families in Kerala. The study's findings indicated a favourable opinion of adolescents' understanding of blood donation. The information obtained was analyzed using the Chi-square test. This study reveals 10% of adolescents have adequate knowledge, 61.70% of adolescents have moderate knowledge and 28.30% of adolescents have inadequate knowledge regarding blood donation. There are three correlations between the knowledge level of adolescents regarding blood donation with their demographic variables like educational status (x2= 10.307), source of knowledge (x2=10.476) and number of invitations (x2=14.47). And there is no correlation between age (x2= 4.260), gender (x2= 2.711) and number of donations (x2= 5.16). Hence the hypothesis is accepted.